TEOREMA TITIK TETAP UNTUK PEMETAAN KANNAN PADA RUANG METRIK MODULAR TERITLAK - Lusi Harini (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2019)
In this paper, we will discuss about fixed point theorems in generalized modular metric space for Kannan- type mapping. The existence of the fixed point of this mapping is guaranteed by providing that the mapping domain is a -finite set and the Kannan- mapping constant satisfied where K is a constant from the axiom of generalized modular metric space.